Pretreatment of Diabetic Adipose-derived Stem Cells with mitoTEMPO Reverses their Defective Proangiogenic Function in Diabetic Mice with Critical Limb Ischemia - Lian, Kun (Cell Transplant, 2019)
Adipose-derived stem cells (ADSCs) have the ability to migrate to injury sites and facilitate tissue repair by promoting angiogenesis. However, the therapeutic effect of ADSCs from patients with diabetes is impaired due to oxidative stress. Given that diabetes is a group of metabolic disorders and mitochondria are a major source of reactive oxygen species (ROS), it is possible that mitochondrial ROS plays an important role in the induction of diabetic ADSC (dADSC) dysfunction. ADSCs isolated from diabetic mice were treated with mitoTEMPO, a mitochondrial ROS scavenger, or TEMPO, a universal ROS scavenger, for three passages. The results showed that pretreatment with mitoTEMPO increased the proliferation, multidifferentiation potential, and the migration and proangiogenic capacities of dADSCs to levels similar to those of ADSCs from control mice, whereas pretreatment with TEMPO showed only minor effects. Mechanistically, mitoTEMPO pretreatment enhanced the mitochondrial antioxidant capacity of dADSCs, and knockdown of superoxide dismutase reduced the restored mitochondrial antioxidant capacity and attenuated the proangiogenic effects induced by mitoTEMPO pretreatment. In addition, mitoTEMPO pretreatment improved the survival of dADSCs in diabetic mice with critical limb ischemia, showing protective effects similar to those of control ADSCs. Pretreatment of dADSCs with mitoTEMPO decreased limb injury and improved angiogenesis in diabetic mice with critical limb ischemia. These findings suggested that short-term pretreatment of dADSCs with a mitochondrial ROS scavenger restored their normal functions, which may be an effective strategy for improving the therapeutic effects of ADSC-based therapies in patients with diabetes.